Impact of Trump’s Phenomenon, Brexit, & Oil Prices Fluctuation Toward Indonesia’s Economic Growth - Abdul Holik (Economics Development Analysis Journal, 2018)
This paper tries to find impact of global uncertainties toward Indonesia’s economic growth. Several problems which will be discussed in this paper namely: impacts of President Donald Trump’s policies, Brexit, and uncertainty regarding crude oil prices. It conducted from 1st quarter of 2010 until 1st quarter of 2017. The method of analysis used here is VECM (Vector Error Correction Model). We use dummy variable to capture the specific change of economic policies when Brexit and Trump’s emergence appear as the major issues which attract attention around the world. We consider these as the uncertainties which influence global society. Based on the result, there is positive impact of economic policy uncertainty in UK in the long-run. When Brexit was taken into account, in the short-run, it also has positive impact toward Indonesia’s economic growth. Meanwhile economic policy uncertainty in the US generates negative impact on Indonesia’s economic growth. But Trump’s emergence in the US presidency produces positive impact in the short-run. Oil price fluctuation as the latest shock in the global context has positive significant impact on Indonesia’s economic growth. We consider these results as ways to find breakthrough in understanding of changing policies from developed countries; that not all of them will contribute to negative matters. The conjecture, hunch, and any speculation must be postponed due to lack of convincing proofs.